2022
DOI: 10.3389/fcell.2022.941539
|View full text |Cite
|
Sign up to set email alerts
|

Implications of High-Density Cholesterol Metabolism for Oocyte Biology and Female Fertility

Abstract: Cholesterol is an essential component of animal cells. Different regulatory mechanisms converge to maintain adequate levels of this lipid because both its deficiency and excess are unfavorable. Low cell cholesterol content promotes its synthesis and uptake from circulating lipoproteins. In contrast, its excess induces the efflux to high-density lipoproteins (HDL) and their transport to the liver for excretion, a process known as reverse cholesterol transport. Different studies suggest that an abnormal HDL meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 123 publications
0
14
0
Order By: Relevance
“…Dyslipidemia, particularly low HDL-C, is a systemic risk factor for many multi-organ failures, such as acute pancreatitis [ 3 ] and sepsis [ 4 ]. In addition, low HDL-C is also associated with reproduction disorders, such as unexplained female infertility [ 5 ] and erectile dysfunction [ 6 ], as well as cardiovascular risk factors. Moreover, in non-alcoholic fatty liver disease (NAFLD), reduced levels of HDL-C may serve as an indicator for the onset of liver cancer in conjunction with hepatic fibrosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia, particularly low HDL-C, is a systemic risk factor for many multi-organ failures, such as acute pancreatitis [ 3 ] and sepsis [ 4 ]. In addition, low HDL-C is also associated with reproduction disorders, such as unexplained female infertility [ 5 ] and erectile dysfunction [ 6 ], as well as cardiovascular risk factors. Moreover, in non-alcoholic fatty liver disease (NAFLD), reduced levels of HDL-C may serve as an indicator for the onset of liver cancer in conjunction with hepatic fibrosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This imbalance can interfere with crucial processes such as oocyte maturation, meiosis arrest and egg activation following fertilization. Consequently, disruptions in HDL-C metabolism could impair FF HDL function, leading to infertility due to dysfunctional and unstable eggs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…APOH and APOM are also associated with HDL function [ 53 ]. It has been reported that abnormal metabolism of HDL and its lipoprotein mutation affect fertility in females and also affect the maturation and embryo quality of oocytes matured in vitro [ 54 , 55 , 56 , 57 ]. HDL is the only major lipoprotein detected in follicular fluid, and HDL plays an important role in ovarian cholesterol transport [ 58 ].…”
Section: Discussionmentioning
confidence: 99%